The Lexical Equivalence in the Translation of the English Noun ‘Love’ into Indonesian - Widiastuti, Ni Made Ayu; Indriani, Ketut Santi (Humanis; Vol 27 No 1 (2023)DO - 10.24843/JH.2023.v27.i01.p02, 2023)
This study aims at finding out the translation variations as the lexical equivalences of the English noun ‘love’ into Indonesian, and analyzing the translation shifts. The data were taken from the parallel corpus containing the English expressions with the noun ‘love’ and their translations. The data were collected through the documentation method and analyzed qualitatively. The results show that the translations of the English noun ‘love’ are varied with 21 lexicons. The translations are categorized into three types, those that are translated into the base words, the affixed words, and the phrases. Besides that, there are also zero translation and borrowing terms used. The TL noun ‘cinta’ is found at 72.2% and it is indeed equivalent with the SL noun ‘love’. The other variations are the synonyms and related lexicons used based on the certain contexts. Two kinds of shifts namely class and unit shifts are found in the translations.